2007
DOI: 10.1016/j.bbrc.2007.05.216
|View full text |Cite
|
Sign up to set email alerts
|

A novel two-step procedure to expand cardiac Sca-1+ cells clonally

Abstract: Resident cardiac stem cells (CSCs) are characterized by their capacity to self-renew in culture, and are multi-potent for forming normal cell types in hearts. CSCs were originally isolated directly from enzymatically digested hearts using stem cell markers. However, long exposure to enzymatic digestion can affect the integrity of stem cell markers on the cell surface, and also compromise stem cell function. Alternatively resident CSCs can migrate from tissue explant and form cardiospheres in culture. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 22 publications
2
60
0
Order By: Relevance
“…Cell surface antigen analysis showed that most CEDCs were Sca-1 + , whereas CDCs were included in both Sca-1 + and c-KIT + CSCs groups. Our findings confirmed previous studies, which reported that Sca-1 + cells had clonogenic potential [31,32] and CDCs were included in both subgroups of CSCs [12,16]. Until now the most important difference of isolated cells was based on expression of surface markers that included CD117 and Sca-1.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cell surface antigen analysis showed that most CEDCs were Sca-1 + , whereas CDCs were included in both Sca-1 + and c-KIT + CSCs groups. Our findings confirmed previous studies, which reported that Sca-1 + cells had clonogenic potential [31,32] and CDCs were included in both subgroups of CSCs [12,16]. Until now the most important difference of isolated cells was based on expression of surface markers that included CD117 and Sca-1.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have been carried out to isolate and characterize cardiac precursor cells (mainly c-Kit + , Sca-1 + , and cardiospheres) from normal and pathologic fetal and adult heart biopsies [12][13][14][15]. Different protocols have been developed to improve CSC isolation methods, resulting in the generation of a specific population of CSCs [16][17][18][19]. In addition to cell sorting and culture of explants, clonogenic expansion of cells has been described as another CSCs isolation method [20].…”
mentioning
confidence: 99%
“…Human cardiospheres were delivered intramyocardially into immunodeficient mice, and significant functional improvement was seen 3 weeks later (fractional shortening 37% in cardiosphere-injected group vs 18% in control group [P <.05] compared to sham 59%) along with vigorous engraftment and cardiogenesis. The cardiosphere culture method has since been used by independent groups to enrich c-Kit + cardiac stem cells 20 and Sca-1 + cardiac stem cells 21 alike for further analysis.…”
Section: Cardiosphere-derived Cardiac Stem Cellsmentioning
confidence: 99%
“…Subsequently, the cells that adhere to the blood vessel endothelium, permeate the vessel walls to access the target tissue. With the help of SDF-1α, the secretion of more MMP-9, NO, and VEGF promote the mobilization of stem cells (Tang et al, 2007;Kuang et al, 2008;Gao et al, 2010;Huang et al, 2010;Takamiya et al, 2011). These paracrine factors, especially VEGF, are important for maintaining or improving normal vascular endothelial function.…”
Section: Discussionmentioning
confidence: 99%